HIV-Associated Vacuolar Myelopathy and HIV-Associated Neurocognitive Disorder as an Initial Presentation in HIV Infection - Md Asaduzzaman; Atonu Das; Sowmitra Das; Mahfuza Khadija Shamma; Abul Kalam Mohammed Shoab; Biplob Kumar Roy (Case Reports in Infectious Diseases)
Several neurological disorders have been described in HIV infection. Vacuolar myelopathy and neurocognitive disorders usually come at an advanced stage of the disease process. Here, we present a case where these features constitute the presenting complaints. Both of these conditions improved significantly following the start of HAART. We believe this clinical pathway can be a good learning point for the clinician.